Intracellular pH regulation by acid-base transporters in mammalian neurons - Ruffin, Vernon A.; Salameh, Ahlam I.; Boron, Walter F.; Parker, Mark D. (Frontiers in Physiology, 2014)
Intracellular pH (pHi) regulation in the brain is important in both physiological and physiopathological conditions because changes in pHi generally result in altered neuronal excitability. In this review, we will cover 4 major areas: [1] The effect of pHi on cellular processes in the brain, including channel activity and neuronal excitability. [2] pHi homeostasis and how it is determined by the balance between rates of acid loading (JL) and extrusion (JE). The balance between JE and JL determine steady-state pHi, as well as the ability of the cell to defend pHi in the face of extracellular acid-base disturbances (e.g. metabolic acidosis). [3] The properties and importance of members of the SLC4 and SLC9 families of acid-base transporters expressed in the brain that contribute to JL (namely the Cl-HCO3 exchanger AE3) and JE (the Na-H exchangers NHE1, NHE3 and NHE5 as well as the Na+- coupled HCO3- transporters NBCe1, NBCn1, NDCBE, and NBCn2). [4] The effect of acid-base disturbances on neuronal function and the roles of acid-base transporters in defending neuronal pHi under physiopathologic conditions.